2021
DOI: 10.3390/v13081594
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Convalescent Plasma Is More than Neutralizing Antibodies: A Narrative Review of Potential Beneficial and Detrimental Co-Factors

Abstract: COVID-19 convalescent plasma (CCP) is currently under investigation for both treatment and post-exposure prophylaxis. The active component of CCP mediating improved outcome is commonly reported as specific antibodies, particularly neutralizing antibodies, with clinical efficacy characterized according to the level or antibody affinity. In this review, we highlight the potential role of additional factors in CCP that can be either beneficial (e.g., AT-III, alpha-1 AT, ACE2+ extracellular vesicles) or detrimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…Fc-dependent functions have important antimicrobial effects, including phagocytosis, complement activation, and antibody-dependent cellular toxicity. 37 Previous studies suggest that the main driver of clinical benefit from convalescent plasma units relies on their neutralising antibody content, 38 and that the cell receptor binding capacity of the Fc-region is preserved after methylene blue treatment. 36 Still, a concern remains that the dye might react with the glycosylation domain and affect Fc-region functionality and thus the overall response.…”
Section: Discussionmentioning
confidence: 99%
“…Fc-dependent functions have important antimicrobial effects, including phagocytosis, complement activation, and antibody-dependent cellular toxicity. 37 Previous studies suggest that the main driver of clinical benefit from convalescent plasma units relies on their neutralising antibody content, 38 and that the cell receptor binding capacity of the Fc-region is preserved after methylene blue treatment. 36 Still, a concern remains that the dye might react with the glycosylation domain and affect Fc-region functionality and thus the overall response.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical utility of CCP While CCP contains a plethora of biologically active molecules (90), we now have very strong evidence that appropriately vetted CCP from eligible convalescent donors is safe for patients (91, 92), with no evidence of increased risks of transfusion-transmitted acute lung injury, antibody-mediated enhancement concerns feared in the early days of the pandemic (93) nor is there evidence that CCP induces accelerated SARS-CoV-2 evolution (11). Polyclonal antibodies such as CCP are likely to offer better protection against onset of variants than monoclonal antibodies (9496): importantly, Pommeret et al showed that CCP can rescue immune escape variants emerged during treatments with bamlanivimab/etesevimab cocktail (97).…”
Section: Resultsmentioning
confidence: 99%
“… 117 However, numerous non-antibody proteins and chemical factors in CCP may drive detrimental outcomes in patients. 118 CCP therapy also raises a flurry of ethical questions. 119 As such, the quality, efficacy and safety of CCP against COVID-19 need to be further investigated and determined.…”
Section: Therapeutic Igm Antibodies Against Sars-cov-2mentioning
confidence: 99%